Strategi Kampanye Public Relations Prepp Studio dalam Mempertahankan Citra Perusahaan - Abdul Hadi; Lilik Sumarni (Institut Nalanda, 2024)
This research is based on the Public Relations Campaign Strategy carried out by Prepp Studio to maintain the Company's image. Competition in the world of local and international brand business is widespread, one of which is Prepp Studio which must be ready to face various challenges in the current market. Therefore, an appropriate and appropriate Public Relations campaign strategy is needed. This research aims to determine the Planning, Implementation and Evaluation used by Prepp Studio's Public Relations Campaign Strategy in maintaining the Company's Image. This research uses a descriptive analysis method with a qualitative approach. The data collection techniques used were interviews, observation and literature study. This research uses the theory of Public Relations Strategy stages, namely Planning, Implementation, and Evaluation. The results of this research are the planning carried out, namely finding the target market and market segmentation, preparing the team, and formulating ideas and targets. Implementation carried out, namely the implementation of what has been formulated, as in the Public Relations Campaign Strategy, preparing advertisements, collaborating with other brands, then create content and giveaways as well as social media updates. The evaluation carried out is monitoring analytical data from targets, as well as public responses, and also holding evaluations which are held once a week, to produce a better company image.